"You have skirted this hill long enough". The tension between rhetoric and history in a Byzantine Piyyut - Lieber, Laura Suzanne (Hebrew Union College annual / Jewish Institute of Religion, 2009)
Yannai, a major liturgical poet of the Byzantine period, generally avoids highly specific references to his contemporary historical situation in his piyyutim (liturgical poems), which were composed for recitation in the synagogues of late antiquity. This lack of unambiguous historical data has made it difficult to date Yannai with much specificity and has, in turn, prevented the easy use of his works in elucidating his historical context. This essay suggests that Yannai's work should be read in the context of the Samaritan Rebellions of the sixth century, specifically in relation to the revolt of 555/556, in which Jews were noted participants. Such an historical context helps uncover specific ideas and nuances within Yannai's writings and also offers insight more generally into this historical period. This study focuses on Yannai's piyyut for the Sabbath when the Torah reading began with Deuteronomy 2:2 (a translation of the poem and a new Hebrew edition are provided as an appendix). This specific poem has been cited previously by some scholars who assume that Yannai witnessed the Samaritan rebellions, but without detailed analysis; this text also demonstrates what can be gained by understanding Yannai as a major Jewish voice of Palestinian Jewish society during the reign of the Emperor Justinian.